Electron-impact dissociation cross sections of vibrationally excited He molecular ion. (9th November 2015) - Celiberto, R; Baluja, K L; Janev, R K; Laporta, V
Abstract: Electron-impact cross sections for the dissociation process of vibrationally excited He molecular ion, as a function of the incident electron energy are calculated for the dissociative transition by using the R -matrix method in the adiabatic-nuclei approximation. The potential energy curves for the involved electronic states and transition dipole moment, also calculated with the R -matrix method, were found to be in good agreement with the results reported in literature. The vibrationally resolved dissociation cross sections of He exhibit a resonant structure around 7 eV. The observed strong variation of the magnitude of this structure with the vibrational level is explained in terms of the overlap of initial and final (continuum) state wave functions in the Franck–Condon region.